Authorial Characters: Written Identities in the work of Goetz, Lottmann, and Herbst (KULT_online, 2015)
Authors often stage themselves in their texts and other public media. The receptive ability to discern between reality and fiction often appears impossible. Terms like staging, representation or embodiment have been used to mark these instances. Kreknin utilizes the literary term autofiction. He emphasizes that the written, autofictional, authorial figures and identities also have to be recognized as actual work to form the authors’ identities in reality. Kreknin verifies his thesis through a study on ‘Poetiken des Selbst’, which he bases on the authors Rainald Goetz, Joachim Lottmann, and Alban Nikolai Herbst. Their poetics include autofictional writings, as well as medial stagings.